A study to explore opinions and attitudes of Saudi Arabian MR professionals on the current status of routine MR scanner quality assurance testing in the Kingdom of Saudi Arabia. Issue 4 (November 2018) - Alsharif, W.; McGee, A.; Rainford, L.; Davis, M.
Abstract: Introduction: Internationally it is recommended that quality assurance (QA) testing of MR systems is the responsibility of MR professionals to ensure efficient scanner performance. This study aims to explore the opinions and attitudes of MR professionals in the Kingdom of Saudi Arabia (KSA) regarding the current status of routine QA testing within MRI departments. Methods: A qualitative approach was adopted, with MR professionals working in public, semi-public and private hospitals in the KSA invited to participate in this interview-based study. A total of 52 individual semi-structured interviews were conducted with purposive sampling of MR radiographers and medical physicists based at 19 major centres across the three main geographical regions in the KSA. Data went through duration of coding following qualitative data analysis framework based on Miles and Huberman's philosophical underpinnings. Results: The findings demonstrated that 89.5% (n = 17) of the MRI departments surveyed rely on the service provided by the equipment vendor in order to ensure ongoing MR scanner performance. Overall, the level of MR radiographer participation in weekly MR scanner QA testing was low (13.3%, n = 3). Lack of legal requirement, professional organisation and knowledge were highlighted as the principal factors limiting radiographer involvement in the weekly MR QA in the KSA. Conclusion: The results of this study support the establishment of a legal requirement and national policy in order to encourage radiographers in the KSA to take an active role in MRI QA testing to enable suboptimal MR scanner performance to be identified before it becomes clinically evident. Highlights: A lack of a legal requirement and policy to carry out weekly MRI QA testing in their departments. The majority of the MRI departments rely on the planned preventive maintenance provided by the equipment vendor. A limited number of MR radiographers were involved in MRI QA testing in their departments.